Minecraft : Guide to Combat - Jelley, Craig; Marsh, Ryan (New York : Del Rey, 2021)
In this fully illustrated guide to combat, Minecrafters will learn how to survive the perils and pitfalls of defending their base.
"Mojang Studios."
Keywords: Minecraft (Game) -- Juvenile literature; Minecraft (Game) -- Handbooks, manuals, etc; Juvenile literature; Video games -- Juvenile literature; Indoor games